2017
DOI: 10.1053/j.jfas.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Functional Medium-Term Results After Autologous Matrix-Induced Chondrogenesis for Osteochondral Lesions of the Talus: A 5-Year Prospective Cohort Study

Abstract: Autologous matrix-induced chondrogenesis (AMIC) has gained popularity in the treatment of osteochondral lesions of the talus. Previous studies have presented promising short-term results for AMIC talar osteochondral lesion repair, a 1-step technique using a collagen type I/III bilayer matrix. The aim of the present study was to investigate the mid-term effects. The 5-year results of a prospective cohort study are presented. All patients underwent an open AMIC procedure for a talar osteochondral lesion. Data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 50 publications
1
34
0
2
Order By: Relevance
“…The FAOS sports score was reported by 2 studies, 35,54 1 study reported on the Foot and Ankle Disability Index (FADI) sports subscale, 8 and 1 study reported on the German Foot Function Index (FFI-D) sports subscale. 25 Because of low reporting, these scores were not further analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…The FAOS sports score was reported by 2 studies, 35,54 1 study reported on the Foot and Ankle Disability Index (FADI) sports subscale, 8 and 1 study reported on the German Foot Function Index (FFI-D) sports subscale. 25 Because of low reporting, these scores were not further analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with our results, most studies about AMIC-treated OLTs could not show any significant influence of these demographical factors. 11,24,47 D’Ambrosi et al 11 performed arthroscopic AMIC in 31 OLTs and did not find any age-related differences. However, the preoperative and final functional results were inferior in the subgroup aged >33 years, which may indicate that the preoperative ankle status is a negatively influencing factor.…”
Section: Discussionmentioning
confidence: 96%
“…Since OLTs are often already symptomatic among young and athletic patients, there is a need for long-term clinical results after AMIC repair. Gottschalk et al 24 reported clinical improvement from 1- to 5-year follow-up, yet no studies examined the clinical outcomes beyond 5 years. In the present study, subgroup analysis revealed a slightly lower mean AOFAS score for patients with follow-up >5 years versus 2 to 5 years (92.5 vs 93.5 points).…”
Section: Discussionmentioning
confidence: 99%
“…Com um acompanhamento mínimo de dois anos, Walther et al, Valderrabano e outros autores relataram excelentes resultados clínicos e radiológicos usando AMIC®, atingindo altas pontuações AOFAS e MOCART (16,17) . Em um estudo de coorte prospectivo muito recente, Gottschalk et al corroboram esses achados, atingindo alta satisfação clínica em um seguimento de 5 anos, o seguimento mais longo da literatura (18) . Os maiores benefícios da técnica foram observados no primeiro ano; no entanto, a satisfação clínica adicional foi atingida após 5 anos.…”
Section: Discussionunclassified
“…Entre as novas alternativas para tratar essas lesões, a Condrogênese Autóloga Induzida por Matriz (AMIC®) provou fornecer resultados satisfatórios em um seguimento de médio prazo (6) . AMIC® combina microfraturas com a aplicação de Chondro-Gide®, uma matriz de dupla camada de colágeno tipo I/III (Geistlich Surgery, Wolhusen, Suíça), usada para estabilizar e proteger o coágulo sanguíneo que resulta das microfraturas do osso subcondral.…”
Section: Introductionunclassified